2009
DOI: 10.1002/ajim.20713
|View full text |Cite
|
Sign up to set email alerts
|

Asbestos exposure and benign asbestos diseases in 772 formerly exposed workers: Dose–response relationships

Abstract: Parenchymal asbestosis and PP are associated with different aspects of asbestos exposure. DPT appears to be less specific for asbestos exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 22 publications
0
19
0
1
Order By: Relevance
“…Numerous studies have examined the dose-or exposureresponse relation for pleural plaques (Bar-Shai et al, 2012;Boffetta, 1998;Clin et al, 2011;Eisenhawer et al, 2014;Ehrlich et al, 1992;Finkelstein & Vingilis, 1984;Hosoda et al, 2008;Jakobsson et al, 1995;Järvholm, 1992;Karjalainen et al, 1994;Lockey et al, 2015;Mastrangelo et al, 2009;McDonald et al, 1986;Moolgavkar et al, 2014;Paris et al, 2008Paris et al, , 2009Rohs et al, 2008;Sandén & Järvholm, 1986;Shepherd et al, 1997;Soulat et al, 1999;Van Cleemput et al, 2001). Results differ among these studies, 6 but exposure variables found relevant in one or more studies include time since first exposure (TSFE), age at first exposure (Jones, 1997), type (Hillerdal, 1997;Jones, 1997;Sandén & Järvholm, 1986) and dimensions of fiber (Hillerdal, 1997;Jones, 1997), lung fiber burden (Karjalainen et al, 1994;Roberts, 1971), duration of exposure, intensity of estimated asbestos exposure and cumulative exposure (measured in various ways).…”
Section: Dose-or Exposure-response and Pleural Plaquesmentioning
confidence: 99%
“…Numerous studies have examined the dose-or exposureresponse relation for pleural plaques (Bar-Shai et al, 2012;Boffetta, 1998;Clin et al, 2011;Eisenhawer et al, 2014;Ehrlich et al, 1992;Finkelstein & Vingilis, 1984;Hosoda et al, 2008;Jakobsson et al, 1995;Järvholm, 1992;Karjalainen et al, 1994;Lockey et al, 2015;Mastrangelo et al, 2009;McDonald et al, 1986;Moolgavkar et al, 2014;Paris et al, 2008Paris et al, , 2009Rohs et al, 2008;Sandén & Järvholm, 1986;Shepherd et al, 1997;Soulat et al, 1999;Van Cleemput et al, 2001). Results differ among these studies, 6 but exposure variables found relevant in one or more studies include time since first exposure (TSFE), age at first exposure (Jones, 1997), type (Hillerdal, 1997;Jones, 1997;Sandén & Järvholm, 1986) and dimensions of fiber (Hillerdal, 1997;Jones, 1997), lung fiber burden (Karjalainen et al, 1994;Roberts, 1971), duration of exposure, intensity of estimated asbestos exposure and cumulative exposure (measured in various ways).…”
Section: Dose-or Exposure-response and Pleural Plaquesmentioning
confidence: 99%
“…During the same period, the average concentration of asbestos in the workplace was equal 7.2 f/ml in 772 past exposed workers in Veneto region of Italy [13]. Since in these subjects the correlations between historical exposure and benign asbestos-related diseases were consistent with those of earlier studies carried out with conventional chest x-rays, the estimates of occupational exposure to asbestos were accurate and precise [13]. Occupational exposure was about three orders of magnitude higher than exposure from natural sources.…”
Section: Discussionmentioning
confidence: 85%
“…During the 24-year history of regulation of exposure to asbestos, the time-weighted average concentration was ((12×2) + (5×9) + (2×13))/24, equal to 7.7 f/ml [12]. During the same period, the average concentration of asbestos in the workplace was equal 7.2 f/ml in 772 past exposed workers in Veneto region of Italy [13]. Since in these subjects the correlations between historical exposure and benign asbestos-related diseases were consistent with those of earlier studies carried out with conventional chest x-rays, the estimates of occupational exposure to asbestos were accurate and precise [13].…”
Section: Discussionmentioning
confidence: 99%
“…Asbestos health monitoring guidelines were published by the Spanish Health Minister in 2003 (24) and by French Haute Autoritè de Santè in 2010 (25). In Italy a consensus document developed by experts was developed in 2012 (13) after several experiences carried out in the previous two decades (5,7,(26)(27)(28)(29)(30)(31)(32)(33). Anyhow, official specific recommendations of the Italian Health Minister are not available yet.…”
Section: Discussionmentioning
confidence: 99%